Designing out Crime at Bus Terminals in Nigeria: An Exploratory Analysis - Christopher A, WOJUADE; Adewumi I, BADIORA (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
Transit stops usually correlate with high human and crime activities. Having obtained information from transport facility managers and users, this study explores crime prevention and perception of safety at Nigerian Bus stations. This study compares and contrasts the perceptions of users and transport service managers in relation to selected bus stations (Ring road and Uselu) in Benin City as a case study. From the perception of the managers, it was believed that both bus stations observed design principles for crime prevention but that of ring road was planned more effectively than Uselu. This suggests that ring road bus stations should be perceived to be safer. Surprisingly, this was not as the users felt the other bus station was slightly safer. An assessment of landuses within 150m radius to each bus station showed that ring road station is someway in close proximity to several landuses likely to generate, attract, and facilitate crime. Hence, we speculate that the activity generated from these landuses may have negatively influenced perceived feeling of safety at this terminal. These findings thus, suggest that the surrounding environment acts to mediate perception of safety and effectiveness of crime prevention strategies of a site. The study therefore, concludes that safety and security planning of a place could be applied better by considering not only the security strategies but also the immediate surrounding environment.